E-books in Directed Reading Lessons and Book Orientation Behaviors of Young Children - Danao, Jonalou S. (Alipato, A Journal of Basic Education, 2018)
This multiple cases study aimed to investigate the use of e-books in directed reading lessons and book orientation behaviors of young children, particularly book handling and story reading. After seeking permission from the author, 14 storybooks from the Little Critter series of Mercer Mayer were translated to Filipino, expert validated, and used in the study. The participants were exposed to 12 one-on-one directed reading lessons, six of which used books in print format while the remaining six used e-books. Results indicated that using e-books in directed reading lessons increased the number of book handling behaviors that children manifested when presented with print books. Story reading behaviors the children manifested increased during the e-book intervention sessions but not after the intervention. Based on the results, it was recommended that young children be allowed to explore and enjoy the benefits of having such technology in learning and developing reading skills in school and at home. They should be allowed to use it with guidance and with limits for educational purposes. Keywords: book orientation behaviors, directed reading lessons, e-books, young children